Penelitian Tafsir dan Pendekatan Kualitatif - Fauzi Fauzi (TAFSE: Journal of Qur'anic Studies, 2019)
This article aims to analyze the interpretation research and the approaching model it uses. Data collection techniques using documentation. The result of the research is that most of the research on the interpretation of the Qur'an is carried out with a qualitative approach by emphasizing the ability and competence of researchers to analyze existing data. Data collection includes documentation techniques. The development of al-Qur'an research and interpretation today also leads to how to examine texts that live in a society whose data collection techniques are addition to documentation, as well as observation and interviews. Interpretation researchers are required to continue to develop themselves to understand aspects of the interpretation methodology related to sources, methods, and perspectives. The current approach is also continuously enriched so that it is able to provide analysis in interpretation research in order to make a contribution of knowledge for the development of science and knowledge. Artikel ini bertujuan menganalisis penelitian tafsir dan model pendekatan yang digunakannya. Teknik pengumpulan data mengunakan dokumentasi. Hasil penelitiannya adalah penelitian tafsir al-Qur’an banyak dilakukan dengan pendekatan kualitatif dengan menekannya kemampuan dan kompetensi peneliti untuk menganalisis data-data yang ada. Pengumpulan data di antaranya dengan dilakukan teknik dokumentasi. Perkembangan penelitian al-Qur’an dan tafsir dewasa ini juga mengarah bagaimana meneliti teks-teks yang hidup dalam masyarakat yang teknik pengumpulan datanya di samping dokumentasi, juga observasi dan wawancara. Peneliti tafsir dituntut untuk terus mengembangkan diri untuk memahami aspek metodologi tafsir baik terkait sumber, metode maupun perspektifnya. Pendekatan kekinian juga terus diperkaya agar mampu memberikan analisis dalam penelitian tafsir agar memberikan contribution of knowledge bagi pengembangan ilmu dan pengetahuan.